The creation and circulation of public geographies. (March 2013) - Kitchin, Rob; Linehan, Denis; O'Callaghan, Cian; Lawton, Philip
In response to the commentaries, we discuss further how social media disrupts and remakes the creation and circulation of geographical knowledges and potentially reconfigures the moral economy of the social sciences. In particular, we examine questions of what is meant by public geography, the publics which such geographies serve, alternative and complementary approaches to social media, the politics of authorship within collective blogs, the politics and mechanisms of knowledge circulation, and the extent to which social media has an impact beyond the academy, enacting 'minimal politics'.